STRATEGI MENGHADAPI CYBERBULLYING DI MEDIA SOSIAL PADA MAHASISWA SEMESTER BARU DI INDONESIA - Isaac Yeremia Nugroho; Kevin Handoyo; Ricky Junianto Wijaya; Claudio Erlisto Candra Juniarto; Fernandi Mahendrasusila (Universitas Kapuas, 2025)
Cyberbullying on social media has become a significant challenge for new semester students in Indonesia, who are still adapting to their new academic and social environments. A lack of awareness and skills in dealing with cyberbullying can negatively impact their mental health and academic performance. This study aims to explore strategies that students can apply in facing cyberbullying, both through preventive and responsive approaches. The research employs a qualitative approach using in-depth interviews and surveys conducted with new semester students at several universities in Indonesia. The findings indicate that students tend to adopt strategies such as limiting social media interactions, enhancing digital literacy, and seeking support from friends and family. The implications of this study are expected to provide recommendations for educational institutions in designing educational programs and policies to help students cope with challenges in the digital world.